#TITLE_ALTERNATIVE# - FRITRIANA NIM : 21816004, RIAN
Efficiency is one of the main criteria underlying company's performance assessment that is a measure of operational excellence or productivity. PT M in scheduling process has not consider the efficiency yet. And to achieve it can be done by sequencing the production processes from the stages of weighing, granulation, mixing, compressing to inspection, so could got the sequence of products that provide most efficient (short) time for the completion time, machine idle time and the product idle time. The most efficient product sequence can be determined through scheduling method based on the SPT (Shortest Processing Time), LPT (Longest Processing Time) and random using standard hours data for each stage of production process. Scheduling method based on SPT is done in 6 schemes, LPT 6 schemes, random in 2 sequences with each sequence are 4 schemes and besides that 1 sequence using SPT method at the beginning of process stage and then sequence of product follow the previous step so that the total sequences are 21 schemes. The result of scheduling using SPT method that is started from weighing stage until mixing then continued with the same sequence until inspection stage gives the shortest (efficient) time for completion time and product iddle time.